The Effects of Financial Information Symmetry on Conflict Resolution: An Experiment in the Context of Labor Negotiations - Nabil Elias (The Accounting Review, 1990)
[Financial information about an organization is normally more accessible to management than to union negotiators. This article deals with the effects of disclosure of this information to union negotiators on the resolution of industrial conflict. This study differs from previous research in that it (1) defines information symmetry as pre-negotiation knowledge of financial information about the entity in which both negotiators have interests, rather than as direct knowledge of the opponents' payoff, (2) is conducted in a union-management bargaining context, and (3) is concerned with both settlements and conflicts. As conditions of information symmetry would be difficult to operationalize and control in the field, a laboratory experiment was used to examine the effects of financial information disclosure (symmetry vs. asymmetry) under two conditions of profitability (profit vs. loss) on pre-negotiation expectations and perceptions, and on negotiation outcomes (settlements and conflicts). In the experiment, a negotiating dyad was formed by assigning one subject a management role and another a union role. In all, 80 subjects forming 40 negotiating dyads participated in the experiment. Profitability took two levels: a profit case or a loss case. Disclosure was manipulated by either providing or withholding historical and forecast financial information to union subjects. A pre-negotiation questionnaire solicited perceptions and expectations of subjects. If subjects did not reach a negotiated settlement, their final impasse offers were submitted for arbitration to a hypothetical arbitrator. A post-negotiation questionnaire was then used to obtain subjects' evaluations and perceptions regarding the company, information, settlement, and opponent. Subjects were rewarded according to the level of negotiated or arbitrated settlement. The results of the experiment generally showed that union subjects' pre-negotiation expectations and conflicts were consistently higher when information was not disclosed to them than in the symmetry case, but expectation differences were statistically significant only in the loss case. As expected, settlements were generally higher in the profit case than in the loss case. Insignificant differences were obtained in post-negotiation conflicts and settlements between the asymmetry and symmetry treatments, possibly for two reasons. First, indirect disclosures by management subjects during negotiation may have been made. Second, as negotiating parties in the symmetry or asymmetry treatments reached an impasse, they may have moved farther apart in anticipation of an arbitrated settlement. As settlements and post-negotiation conflicts seemed unaffected by disclosure, an implication of the findings is that unions might benefit by investigating the decision value of the financial information they seek, while management need not automatically assume that information disclosure would make it worse off.]